Herpes Simplex Virus 2 in Autonomic Ganglia: Evidence for Spontaneous Reactivation - Pieknik, Julianna R. (J Virol, 2019)
Herpes simplex virus 2 (HSV-2) can be transmitted in the presence or absence of lesions, allowing efficient spread among the general population. Recurrent HSV genital lesions are thought to arise from reactivated latent virus in sensory cell bodies of the dorsal root ganglia (DRG). However, HSV-2 has also been found latent in autonomic ganglia. Spontaneous reactivation or a low level of chronic infection could theoretically also occur in these peripheral nervous tissues, contributing to the presence of infectious virus in the periphery and to viral transmission. Use of a recently described, optimized virus with a monomeric mNeonGreen protein fused to viral capsid protein 26 (VP26) permitted detection of reactivating virus in explanted ganglia and cryosections of DRG and the sacral sympathetic ganglia (SSG) from latently infected guinea pigs. Immediate early, early, and late gene expression were quantified by droplet digital reverse transcription-PCR (ddRT-PCR), providing further evidence of viral reactivation not only in the expected DRG but also in the sympathetic SSG. These findings indicate that viral reactivation from autonomic ganglia is a feature of latent viral infection and that these reactivations likely contribute to viral pathogenesis. IMPORTANCE HSV-2 is a ubiquitous important human pathogen that causes recurrent infections for the life of its host. We hypothesized that the autonomic ganglia have important roles in viral reactivation, and this study sought to determine whether this is correct in the clinically relevant guinea pig vaginal infection model. Our findings indicate that sympathetic ganglia are sources of reactivating virus, helping explain how the virus causes lifelong recurrent disease.